Estudo do desempenho de componentes baseados em fibras ópticas especiais: fibras de cristal fotônico e de metamateriais e suas aplicações em comunicações - Queiroz, Alex Sander Barros (2015)
In this paper we present a numerical study of the Sagnac interferometer based on photonic crystals and optical coupler metamaterial. In the simulation of the interferometer effects of light propagation were analyzed, considering the dispersion of the group velocity (GVD) and third order (TOD), intrapulse Raman scattering, self-slope (self-steepening) and self-modulation phase in the generalized non-linear Schrödinger equation. The first time the study was conducted for four power division ratio of factors incident in one of the device ports and three dimensions for the device ring length. To characterize the system performance, were analyzed the transmission curves, extinction ratio, crosstalk and compression factor of the transmitted pulse. In the second moment, the performance of the non-linear switching was observed for obtaining gate under Pulse Amplitude Modulation (PAM). Exciting the two device input ports with logical levels "0" and "1", observing their behavior in one of the device outputs. Initially, the modulation is varied adjustment parameter (| ε |), obtaining only the logical OR gate. And in a second application, the fixed modulation parameter remained and was varied the phase of the input ports 0 to 2π rad, lying type logic gate OR, AND and XOR. The characteristics of a metamaterial guide that has the real part of electrical permittivity and magnetic permeability negatives were also studied. This metamaterial guide is coupled to a conventional guide, observing the transmission characteristics and critical power of this type of coupler and compared with a conventional coupler. For this analysis we used a decreasing automodulation profile linearly with five minimum, observing a hysteresis behavior.